2021
DOI: 10.1101/2021.12.01.470730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking Geometric Deep Learning for Cortical Segmentation and Neurodevelopmental Phenotype Prediction

Abstract: The emerging field of geometric deep learning extends the application of convolutional neural networks to irregular domains such as graphs, meshes and surfaces. Several recent studies have explored the potential for using these techniques to analyse and segment the cortical surface. However, there has been no comprehensive comparison of these approaches to one another, nor to existing Euclidean methods, to date. This paper benchmarks a collection of geometric and traditional deep learning models on phenotype p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 96 publications
0
35
0
Order By: Relevance
“…Subsequently, surfaces were then resampled to a sixth-order icosahedral mesh of 40,962 equally spaced vertices. Experiments were run on both template-aligned data and unregistered (native) data, and train/test/validation splits parallel those used in [32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, surfaces were then resampled to a sixth-order icosahedral mesh of 40,962 equally spaced vertices. Experiments were run on both template-aligned data and unregistered (native) data, and train/test/validation splits parallel those used in [32].…”
Section: Resultsmentioning
confidence: 99%
“…2) Training: The task of GA prediction is arguably more complicated than the PMA task, as it is run on scans acquired around term-equivalent age (37−45 weeks PMA) for both term and preterm neonates, and therefore is highly correlated to PMA at scan. Previous work by [32] have shown the benefit of deconfounding the scan age for the task of birth age prediction, where for all gDL methods an additional 1D convolution was used to incorporate scan age as a confound, before the last fully connected layer used to make the birth age prediction. Here, a deconfounding strategy was employed where the scan age information was incorporated into the patch sequence by adding an extra embedding to all patches in the sequence before the transformer encoder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When learning registrations for S3Reg, this generates distortions that must be corrected through averaging warps learned across multiple rotated orientations of the sphere. Recent work showed that contrary to Spherical U-Net, MoNet convolutions (learned from a mixture of Gaussian kernels) could indeed be trained to be rotationally equivariant [9]. Therefore, we develop a new framework for spherical cortical registration based on MoNet, which also takes inspiration from deep-discrete registration frameworks [15,16] designed to learn larger deformations than deep regression frameworks.…”
Section: Introductionmentioning
confidence: 99%